Analysis of Steering Wheel Heavy Komatsu Dump Truck Unit (HD) 785-7 - Hasan Basri; Ery Diniardi; Kisman H Mahmud; Syawaluddin Syawaluddin; Firmansyah Firmansyah (Journal of Applied Sciences and Advanced Technology, 2019)
Steering system is a system control unit that is used for deflecting the direction of motion straight into to the left or to the right in accordance with the will of the operator. At 785-7 HD unit using the steering system type full hydraulic steering valve, where steering valve serves as a directional control valve to direct the oil flow at the time of engine working (pump work), whereas when the engine died steering valve will serve as a hand pump and directional control valve. Abnormaly steering wheel because there is a scratch on spool demand valve causing internal leakage in the demand valve so oil pressure which served as the pilot sensing to move the spool valve is a pressure demand would drop because there is a leak and could not afford to drive the spool until the full open- as a result the oil flow from the steering pump cannot be fully prioritized to steering valve to be forwarded to the steering cylinder.